Exponential decay and well-posedness for a one-dimensional porous-elastic system with distributed delay. Issue 14 (26th October 2021) - Khochemane, Houssem Eddine; Bouzettouta, Lamine; Guerouah, Amin
Abstract : In this paper, we consider a one-dimensional porous-elastic system with distributed delay term acting on the porous equation. Under suitable assumptions on the weight of distributed delay, we establish the well-posedness of the system by using semigroup theory and we show that the dissipation given by this complementary control stabilizes exponentially the system for the case of equal speeds of wave propagation.